Enhanced gut microbiome supplementation of essential amino acids in Diploptera punctata fed low-protein plant-based diet - Ayayee, Paul A.; Petersen, Nick; Riusch, Jennifer; Rauter, Claudia; Larsen, Thomas (Frontiers in Insect Science, 2024)
Building on our previous work, we investigate how dietary shifts affect gut microbial essential amino acid (EAA) provisioning in the lactating cockroach Diploptera punctata. To that end, we fed cockroaches three distinct diets: a plant-only Gari diet composed of starchy and granulated root tuber Yucca (Manihot esculenta), a dog food diet (DF), and a cellulose-amended dog food (CADF) diet. We anticipated that the high carbohydrate, low protein Gari would highlight increased microbial EAA supplementation to the host. By day 28, we observed distinct profiles of 14 bacterial families in the insect gut microbiomes of the three dietary groups. CADF-fed insects predominantly harbored cellulolytic and nitrogen-fixing bacteria families Streptococcaceae and Xanthomonadaceae. In contrast, Gari-fed insects were enriched in anaerobic lignocellulolytic bacteria families Paludibacteraceae and Dysgonomonadaceae, while DF-fed insects had a prevalence of proteolytic anaerobes Williamwhitmaniaceae and sulfate-reducing bacteria Desulfovibrionaceae. Furthermore, we confirmed significantly higher EAA supplementation in Garifed insects than in non-Gari-fed insects based on δ 13 C-EAA offsets between insect and their diets.The δ 13 C-EAA offsets between DF and CADF were nearly indistinguishable, highlighting the relevance of using the plant-based Gari in this experiment to unequivocally demonstrate this function in this insect. Finally, these results were underscored by lower standard metabolic rate (SMR) relative to the DF insect in Gari-fed (intermediate SMR and dietary quality) and CADF (least SMR and dietary quality) insects. The influence of diet on EAA provisioning and SMR responses in insects underscores the need for further exploration into the role of gut microbial functions in modulating metabolic responses.